Fourier coefficients of Eisenstein series formed with modular symbols and their spectral decomposition - Bruggeman, Roelof; Diamantis, Nikolaos (Elsevier, 2016)
The Fourier coefficient of a second order Eisenstein series is described as a shifted convolution sum. This description is used to obtain the spectral decomposition of and estimates for the shifted convolution sum.